2010
DOI: 10.4088/jcp.08m04995gre
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled Study of Quetiapine and Lithium Monotherapy in Adults in the Acute Phase of Bipolar Depression (EMBOLDEN I)

Abstract: clinicaltrials.gov Identifier: NCT00206141.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
273
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(296 citation statements)
references
References 0 publications
12
273
2
2
Order By: Relevance
“…Pooled analyses of five identically designed trials demonstrated that quetiapine was superior to placebo, and moreover was equally effective for acute depression in BDI and BDII 243, 437. The latter finding must be reconciled with the fact that quetiapine beat placebo in only three of the five individual trials in patients with BDII, compared to all five in patients with BDI 253, 290, 438, 439, 440. This is probably because the smaller sample of BDII patients—only about half as many patients with BDII as BDI were enrolled in each of the trials—provided less statistical power for BDII.…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…Pooled analyses of five identically designed trials demonstrated that quetiapine was superior to placebo, and moreover was equally effective for acute depression in BDI and BDII 243, 437. The latter finding must be reconciled with the fact that quetiapine beat placebo in only three of the five individual trials in patients with BDII, compared to all five in patients with BDI 253, 290, 438, 439, 440. This is probably because the smaller sample of BDII patients—only about half as many patients with BDII as BDI were enrolled in each of the trials—provided less statistical power for BDII.…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…The NICE [16] and CANMAT [11] guidelines now recommend QTP as the first-line drug, especially for the more severe pathophysiology of acute mania, due to its rapid and potent antimanic effects. Meanwhile, the efficacy of QTP monotherapy in acute bipolar depression has been consistently confirmed by such double-blind, placebo-controlled studies as BOLDER (BipOLar DEpRession) I/II [8,20] and EMBOLDEN (Efficacy of Monotherapy SEROQUEL in BipOLar DEpressioN) I/II [17,21]. The latter EMBOLDEN studies also examined the efficacy of QTP monotherapy in relapse prevention for bipolar disorders, and the results suggested that the preventive effect of QTP monotherapy is superior to that of placebo for both manic and depressive recurrence, and is superior to that of Li for depressive recurrence [11], and that the efficacy of Li or VPA for relapse prevention of any mood episode is clearly augmented by QTP coadministration [10,22].…”
Section: Qtpmentioning
confidence: 85%
“…In the acute treatment of bipolar disorders, Li alone exhibits modest and limited antidepressive or antimanic effects, but may not be sufficiently applicable to more severe psychopathology, in which combination therapy or replacement with other mood-stabilizing agents might be a better option [15,16]. Meanwhile, some doubt has been cast on the acute antidepressive efficacy of Li by a meta-analytic review [6] that included recent randomized controlled studies [17], since these effects had been observed in small-sized observational studies with relatively short-term follow-up periods. As a result, the latest guideline by the World Federation of Societies of Biological Psychiatry (WFSBP, 2010) does not recommend Li monotherapy as the first-line treatment in acute bipolar depression [13].…”
Section: All-around Mood Stabilizers (Li Qtp Olz) 1 LImentioning
confidence: 99%
“…33 Again, quetiapine 300mg or 600mg daily was superior to placebo at week eight but neither lithium nor paroxetine showed statistically significant separation from placebo in improvement in MADRS total score at endpoint. 32,33 Relapse prevention The continuation phases of the above two studies demonstrated that the effect of quetiapine in bipolar depression is maintained, with the proportion of patients remaining free of either depressive or manic episodes over a period of 400 days being greater in those continuing on quetiapine than those randomised to placebo. 32,33 Similarly, in bipolar I patients, stabilised on either lithium or valproate, continued adjunctive treatment with quetiapine was associated with a significantly increased time to recurrence of either mania or depression compared with adjunctive placebo.…”
Section: How Effective Are Atypical Antipsychotics?mentioning
confidence: 99%
“…30,31 The efficacy of quetiapine monotherapy in bipolar depression was further confirmed in two similarly designed studies each with an eight-week acute phase followed by a continuation phase. 32,33 Both had active reference compounds, lithium 32 or paroxetine. 33 Again, quetiapine 300mg or 600mg daily was superior to placebo at week eight but neither lithium nor paroxetine showed statistically significant separation from placebo in improvement in MADRS total score at endpoint.…”
Section: How Effective Are Atypical Antipsychotics?mentioning
confidence: 99%